A review concerning the main factors that interfere in the electrical percolation threshold content of polymeric antistatic packaging with carbon fillers as antistatic agent. Issue 2 (3rd June 2021) - Vieira, Leonardo de Souza; dos Anjos, Erick Gabriel Ribeiro; Verginio, Gleice Ellen Almeida; Oyama, Isabela Cesar; Braga, Natália Ferreira; da Silva, Thaís Ferreira; Montagna, Larissa Stieven; Passador, Fabio Roberto
Abstract: The use of high contents of carbon fillers in polymeric composites may decrease the mechanical properties of the polymeric matrices, as well as reduce their processability and increase the production costs of antistatic packaging used in the electronic industry. Therefore, it is of great technological interest the research on alternative approaches to produce polymer composites with low electrical percolation threshold. In this way, this review article focuses on the discussion of the main factors that interfere in the electrical percolation threshold of electrically conductive polymer composites, such as the aspect ratio of the carbon fillers and its particle size, the compatibility between the composite phases, the crystallinity degree of the polymeric matrix, the processing route and the location of fillers in multi‐phase polymer blends. Additionally, the review article reports the latest studies related to the obtainment of polymer composites with low percolation threshold contents and produced with different types of carbon fillers. Abstract : Many factors interfere in the percolation threshold content of polymer composites for antistatic applications, such as the aspect ratio of the fillers and their particle size, the compatibility between the composite phases, the crystallinity degree of the polymeric matrix, the processing route and the location of fillers in multi‐phase polymer blends.